Basic Protein Modules Combining Abscisic Acid and Light Signaling in Arabidopsis - Bulgakov, Victor P.; Koren, Olga G. (Frontiers in Plant Science, 2022)
It is generally accepted that plants use the complex signaling system regulated by light and abscisic acid (ABA) signaling components to optimize growth and development in different situations. The role of ABA–light interactions is evident in the coupling of stress defense reactions with seed germination and root development, maintaining of stem cell identity and stem cell specification, stem elongation and leaf development, flowering and fruit formation, senescence, and shade avoidance. All these processes are regulated jointly by the ABA–light signaling system. Although a lot of work has been devoted to ABA–light signal interactions, there is still no systematic description of central signaling components and protein modules, which jointly regulate plant development. New data have emerged to promote understanding of how ABA and light signals are integrated at the molecular level, representing an extensively growing area of research. This work is intended to fill existing gaps by using literature data combined with bioinformatics analysis.